Faktor risiko kejadian stunting pada balita usia 12–59 bulan di kota banjarbaru: studi kasus-kontrol - Hidayat, Rahmat; Khaira, Dicky Septiannoor; Sari, Putri Kartika; Rahman, Andri Nur; Puspawati, Puspawati (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Stunting is a growth failure condition in toddlers caused by chronic malnutrition, impacting physical and cognitive development as well as national productivity. In Banjarbaru City, stunting prevalence significantly decreased from 22,1% to 10,3% in 2023, likely due to factors such as high exclusive breastfeeding coverage, good maternal nutritional status, and adequate access to health services and sanitation.Objective: To analyze factors influencing the reduction of stunting in Banjarbaru City to support effective stunting prevention policies.Methods: The study was conducted in six public health center working areas with the lowest performance in Banjarbaru City in April 2024. This retrospective population-based case-control study involved children aged 12 to 59 months with stunting as cases and normal children as controls. Sample size was calculated using OpenEpi with a total of 78 samples in a 1:2 ratio. Cluster random sampling was used, and data were analyzed using chi-square tests or Fisher’s exact test when chi-square assumptions were not met.Results: The study found that only maternal anemia during pregnancy showed a significant association with stunting after controlling for other variables, with more than six times increased risk (aOR=6,54; 95% CI: 1,79–23,92; p=0,004). This indicates that maternal anemia is the dominant risk factor influencing stunting incidence in Banjarbaru.Conclusion: Maternal anemia affects stunting occurrence in Banjarbaru City, with pregnant women without anemia having a 7,5 times greater chance of having children who are not stunted.s.